2007
DOI: 10.1103/physrevd.75.063511
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the radiative decay of sterile neutrino dark matter from the unresolved cosmic and soft x-ray backgrounds

Abstract: We present upper limits on line emission in the Cosmic X-ray background (CXB) that would be produced by decay of sterile neutrino dark matter. We employ the spectra of the unresolved component of the CXB in the Chandra Deep Fields North and South obtained with the Chandra CCD detector in the E = 0.8 − 9 keV band. The expected decay flux comes from the dark matter on the lines of sight through the Milky Way galactic halo. Our constraints on the sterile neutrino decay rate are sensitive to the modeling of the Mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(153 citation statements)
references
References 66 publications
(81 reference statements)
2
151
0
Order By: Relevance
“…During the last year a number of works appeared, devoted to search for the decay signal of a DM candidate -sterile neutrino -in the X-ray spectra of astrophysical objects [1,2,3,4,5,6,7,8,9]. Indeed, it was noticed long ago [10] that a right-handed neutrino with its mass in the keV range presents a viable warm dark matter (WDM) candidate.…”
Section: Sterile Neutrino As Wdm Candidatementioning
confidence: 99%
See 1 more Smart Citation
“…During the last year a number of works appeared, devoted to search for the decay signal of a DM candidate -sterile neutrino -in the X-ray spectra of astrophysical objects [1,2,3,4,5,6,7,8,9]. Indeed, it was noticed long ago [10] that a right-handed neutrino with its mass in the keV range presents a viable warm dark matter (WDM) candidate.…”
Section: Sterile Neutrino As Wdm Candidatementioning
confidence: 99%
“…To improve the existing bounds on DM parameters [1,2,3,4,5,6,7,8,9] using these instruments, one can look for the sources with optimized "signal-to-noise" ratio (as e.g. dwarf galaxies [3]) and study them with prolonged observations.…”
Section: Sensitivity Of X-ray Telescopes For Dm Detectionmentioning
confidence: 99%
“…Such systems already considered include the dark blobs in merging clusters Riemer-Sørensen et al 2007;Abazajian et al 2007) or simply looking out through our own Milky Way halo (Riemer-Sørensen et al 2006;Boyarsky et al 2006b). However, it was demonstrated that the optimal place to search for the decay line of the sterile neutrino is from the dwarf galaxies of our Milky Way such as Ursa Minor, Draco etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since the DM decay almost at rest, the decay line is very narrow and easily searched for in X-ray and soft gamma ray observations Riemer-Sørensen et al 2007;Abazajian et al 2007;Riemer-Sørensen et al 2006;Boyarsky et al 2006bBoyarsky et al , 2007bAbazajian et al 2001b;Boyarsky et al 2006aBoyarsky et al , 2008dYüksel et al 2008;Watson et al 2006;Loewenstein et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The decay rate of any dark matter candidate with a radiative two-body decay can be constrained from observations of dark matter concentrations (for references see [11][12][13][14][15][16][17][18]). The strongest constraints are obtained from studying dark matter dominated regions, and with instruments with high spectral resolution since the decay line is expected only to suffer negligible broadening due to motion of the dark matter.…”
Section: Introductionmentioning
confidence: 99%